Dragging Drag: The Performance of Gender and Sexuality in the Cook Islands - Alexeyeff, Kalissa (The Australian journal of anthropology, 2000)
Kia Orana day is an annual event on the island of Aitutaki. It consists of performances from a number of government departments to an audience of locals and the occasional tourist. The Kia Orana day described here featured a drag show by the Ministry of Outer Islands Development. Drag shows are prevalent in the Cook Islands and they are performed by both ‘heterosexual’ and ‘homosexual’ men. This paper explores some of the reasons for their popularity through an examination of gendered ideologies that structure Cook Islands social life—in particular the ways in which gender is embodied in everyday movement and dance. The examination of forms of sexuality and gender presented in public life are used to explain the comic currency of drag. I present a number of different interpretations of the Kia Orana performance and suggest that although it may have a similar appearance to Western drag, it has different meanings in the Cook Islands. These meanings suggest drag revolves around notions of gender which are not necessarily defined by sexuality. Cook Islands drag, I propose, must be contextualised in terms of Cook Islands notions of personhood.